Pengaruh Digital Experience Dan Kepercayaan Terhadap Loyalitas Pemain Gen z Pada Platform Mobile Legends: Peran Mediasi Kepuasan Pemain - Deni Marsha; Erick Karunia; Muh. Irfandy Azis; Aswan Aswan; Muhammad Rully Febrian (Universitas Muhammadiyah Bengkulu, 2026)
This study investigates the impact of Digital Experience and Trust on the loyalty of Generation Z players in Mobile Legends: Bang Bang, with Player Satisfaction as a mediator. Using a quantitative approach and PLS-SEM analysis of 100 active Gen Z players in Indonesia, the results show that while Digital Experience and Trust significantly enhance satisfaction and loyalty, Player Satisfaction surprisingly exerts a significant negative effect on loyalty. This indicates a satisfaction paradox where satisfaction acts as a competitive mediator; rising expectations among digital natives reduce satisfaction's effectiveness in driving long-term commitment. Theoretically, this highlights a shift in the role of satisfaction in high-tech markets. Practically, developers should prioritize building trust and continuous digital innovation over merely increasing satisfaction to retain Gen Z players